Perbandingan Senam Tai Chi dan Senam Diabetes Mellitus terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II - Rika Srywahyuni; Agung Waluyo; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the comparison of Tai Chi and DM exercises to reduce blood sugar levels in type II DM patients at Menjalin Health Center. The research design used was a Quasi experiment with a pre and post test group design approach. The results of the study using the Wilcoxon test in the Tai Chi group obtained the value of p = 0.000 <α = 0.05 and the results of the t-test paired sample test on diabetes mellitus exercise obtained p = 0.000 <α = 0.05. In conclusion, Tai Chi and DM exercises are equally influential in reducing blood sugar levels in type II diabetes mellitus patients, however, seen from the difference in decreasing blood sugar levels, Diabetes Mellitus exercise is more effective than Tai Chi exercise. Keywords: Blood Sugar Levels, Diabetes Mellitus Exercise, Tai Chi Exercise